Implementation of the Digital Madrasah Program in Supporting Digital Transformation in the Madrasah Environment (A Case Study at MAN 3 Ngawi): Implementasi Program Madrasah Digital Dalam Mendukung Transformasi Digital di Lingkungan Madrasah (Studi Kasus di MAN 3 Ngawi) - Sari, Irma Lupita; Babyta, Babyta Priyanka Aishwarya; Abu, Abu Darda; Ayu, Ayu Era Wardhani (ABHATS: Jurnal Islam Ulil Albab, 2026)
Digital transformation in the education sector is currently an urgent matter, especially after the changes in learning patterns following the pandemic, which require educational institutions to be more adaptive and responsive to technological developments. The Ministry of Religious Affairs of the Republic of Indonesia, through various educational policies, has promoted the implementation of the Digital Madrasah Programme as a strategic innovation to create modern, adaptive madrasahs that are relevant to the needs of the times. MAN 3 Ngawi is one of the schools in Ngawi that has implemented the digital madrasah programme. This study aims to explore the implementation of the Digital Madrasah Programme in supporting digital transformation at MAN 3 Ngawi, as well as to analyse the supporting and inhibiting factors. The method used is descriptive qualitative research with a case study approach, involving interviews, observations, and documentation as data sources. The results show that the digital madrasah programme increases the effectiveness of learning, facilitates access to materials, and supports digital-based administrative management. The success of the implementation is influenced by the commitment of madrasah leaders, the availability of digital facilities and infrastructure, teacher training, and positive responses from students, despite technical obstacles such as network stability and variations in teacher abilities. [Transformasi digital di sektor pendidikan saat ini merupakan hal yang mendesak, terutama setelah perubahan pola pembelajaran pascapandemi yang menuntut lembaga pendidikan untuk menjadi lebih adaptif dan responsif terhadap perkembangan teknologi. Kementerian Agama Republik Indonesia, melalui berbagai kebijakan pendidikan, telah mempromosikan implementasi Program Madrasah Digital sebagai inovasi strategis untuk menciptakan madrasah yang modern, adaptif, dan relevan dengan kebutuhan zaman. MAN 3 Ngawi adalah salah satu sekolah di Ngawi yang telah menerapkan program madrasah digital tersebut. Penelitian ini bertujuan untuk mengeksplorasi implementasi Program Madrasah Digital dalam mendukung transformasi digital di MAN 3 Ngawi, serta menganalisis faktor pendukung dan penghambatnya. Metode yang digunakan adalah penelitian kualitatif deskriptif dengan pendekatan studi kasus, yang melibatkan wawancara, observasi, dan dokumentasi sebagai sumber data. Hasil penelitian menunjukkan bahwa program madrasah digital meningkatkan efektivitas pembelajaran, mempermudah akses ke materi, dan mendukung pengelolaan administrasi berbasis digital. Keberhasilan implementasi dipengaruhi oleh komitmen pimpinan madrasah, ketersediaan sarana dan prasarana digital, pelatihan guru, serta respon positif dari siswa, terlepas dari adanya kendala teknis seperti stabilitas jaringan dan variasi kemampuan guru.]